Validation of Pedi-IKDC scale and intercultural adaptation to Ukrainian language - Yakushkin, Yevgen; Katsalap, Yelizaveta; Khmyzov, Sergij (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
There are no questionnaires available in Ukrainian that can be used to objectify the results of treatment of orthopaedic and traumatological pathology of the knee joint in children. In world practice, subjective Pedi-IKDC and KOOS-Child scales are used for this purpose. Objective. Validation, intercultural adaptation and translation of the Pedi-IKDS scale in English (original) into Ukrainian for paediatric patients. Methods. Translation and adaptation agreed with the copyright holder of the AOSSM test and performed according to the requirements of the Recommendations for the Cross-Cultural Adaptation of Health Status Measures of the American Academy of Orthopaedic Surgeons Institute for Work & Health. The translated and adapted questionnaire has been tested on a heterogeneous group of 10 children treated for knee pathology. The questionnaire has been adjusted. The participants (both sexes, aged 10–18 years) have been divided into two groups for validation: I — without knee pathology, tested once; II — with knee injuries and physical limitations, tested before and after treatment. Results. We obtained 50 questionnaires in group I (50 children). Student's t-test has been chosen for the analysis of results. To compare the accuracy of the translation, a comparison has been made with the results of A.Y. Nasreddine's study (unpaired Student's t-test). The resulting differences between the original questionnaire and its translation have not been statistically significant (p = 0.966). Group II received 200 questionnaires. A paired Student's t-test has been chosen for analysis. Test results before and after treatment have been significantly different (t2 > tcrit, p < 0.001). The appropriateness and objectivity of the Pedi-IKDC questionnaire have been confirmed. Conclusions. The Pedi-IKDC test has been successfully translated into Ukrainian and adapted for use. The quality of adaptation has been confirmed and no statistically significant difference has been found compared to the results of the world studies. Pedi-IKDC is recommended to be used in children with knee pathology for clinical and scientific purposes.